1ISG-018 Application of a time slot model in oncology: delivery planning and process optimisation. (24th March 2020) - Bertino, C; Di Gerardo, M; Pirrone, A; Dalla Fontana, E; Caravella, G; Spagnuolo, A; Cursano, R
Abstract : Background and importance: Initially, the aim of centralisation of the management of antiblastic drugs was for the quality of preparations, workers' protection, patient safety and reduction of the risks associated with environmental contamination. In recent years, optimisation of hospital processes has become more relevant. In 2017, a new time slot model for the delivery of cancer therapies was introduced in the galenic preparation laboratory. This type of model consists of time slots defined on the basis of fixed criteria. Aim and objectives: The aim was to optimise the management of anticancer drugs. Material and methods: A pharmacoeconomic analysis was carried out on anticancer therapies administered in two oncology departments, one of which was located 20 km from the preparation site. Various parameters were taken into consideration: costs and chemical–physical stability of the drugs, average number of daily dosing and duration of dosing. According to these parameters, five time slots were identified for the oncology on site (8.00, 9.30, 10.00, 12.00 and 14.00) and three time slots for the off-site (14.00 on the previous day, 10.00 and 11.00). High cost therapies can only be set up on the same day for reasons of economic sustainability and to avoid waste. Results: For the time slot 8.00 on site and 14.00 off-site the following were chosen: low cost drugs, with good chemical–physical stability, long term administration, with a maximum of six therapies on site and four off-site. These therapies are set up the day before administration. Time slot 9.30 on site and 10.00 off site: preferably medium and high cost drugs, long term, with a maximum of three therapies on site and eight off site. Time slot 10 on site: medium and high cost drugs, medium or long term, with a maximum of six therapies. Time slot 12.00 on site and 11.00 off site: medium and high cost drugs, medium or short term, for patients who cannot undergo tests and medical examination the previous day. Time slot 14.00 on site: medium and high cost drugs, short term, for patients who cannot undergo tests and medical examination the previous day. Conclusion and relevance: The introduction of a time slot model has led to advantages such as optimisation of time delivery, reduction of waiting times for patients, better communication and improvement in the occupancy rate of chairs in the day hospital. References and/or acknowledgements: No conflict of interest.